Let's get to the nitty gritty : the autobiography of Horace Silver - Silver, Horace, 1928-2014 (University of California Press, 2006)
Horace Silver is one of the giants from the incredible flowering and creative extension of bebop music that became known as "hard bop" in the 1950s. This autobiography of the great composer, pianist, and bandleader takes us from his childhood in Norwalk, Connecticut, through his rise to fame as a musician in New York.